What makes an athlete? A scoping review: Assessing the use of the word athlete with anterior cruciate ligament rehabilitation review studies. Is there a standard? - Byrne, C.; Ward, M.; Saeedi, S.; Obuseh, E. (Scandinavian Journal of Medicine & Science in Sports, 2024)
The term athlete does not currently have an agreed definition or standardized use across the literature. We analyzed the use of the term "athlete" amongst review studies specific to Anterior Cruciate Ligament (ACL) rehabilitation to investigate if the term was justified in its use. A comprehensive review of a database was performed to identify review papers which used the term "athlete" in the title, and which were related to ACL rehabilitation and surveillance. These papers were analyzed and their source papers were extracted for review. Twenty-eight review papers were identified. Source studies were extracted and analyzed. After removal of duplicates 223 source papers were identified. Despite using the term "athlete" in the review study titles only 5/17 (10.7%) sufficiently justified the use of this term. The term athlete was used in 117/223 (52.5%) of the source studies. Of those, 78/117 source studies (66.7%) justified the term athlete. The remaining 39/117 (33.3%) papers where participants were stated to be athletes, gave no justification. The ambiguous use of the term athlete amongst published studies highlights the need for a definition or justification of the term to be used in studies. The lack of a standard definition leads to the potential for studies to dilute high quality data by the potentially differing rehabilitation requirements and access to resources available to those with varying exercise levels. The indiscriminate use of the term athlete could lead to participants with widely ranging physical activity levels being included in the same study, and being used to create clinical advice for all. Advice could potentially vary across those of differing physical activity levels.